2015
DOI: 10.1017/s0033291715000690
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual and physical abuse: age at exposure modulates impact on functional outcome in early psychosis patients

Abstract: Our results suggest a link between exposure to SPA and the later impairment of social functioning before the onset of the disease. EP patients exposed to SPA before age 12 may present long-lasting functional impairment, while patients exposed at a later age may improve in this regard and have a better functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
88
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 62 publications
13
88
4
3
Order By: Relevance
“…In contrast to several previous studies [26,15, 17, 2728] we did not find higher rates of childhood trauma in patients compared with matched controls. However, this may be explained by the fact that the rates of childhood trauma documented in both patients and controls in this study were generally higher than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to several previous studies [26,15, 17, 2728] we did not find higher rates of childhood trauma in patients compared with matched controls. However, this may be explained by the fact that the rates of childhood trauma documented in both patients and controls in this study were generally higher than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In comparison, in a UK-based study, 16% of first episode psychosis patients and 13% controls reported severe sexual abuse and 24% patients and 13% controls reported severe physical abuse [26]. In a study conducted in Switzerland, 12% patients reported sexual abuse and 17.7% reported physical abuse [17]. Our findings are consistent with those of a meta-analysis that compared rates of childhood trauma across countries and found that that Lower and Middle Income Countries (LMIC) had higher rates than upper income countries [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when adjusting all analysis for gender, the differences we observed remained significant, suggesting exposure to trauma is indeed an important characteristic of such patients. In line with others [39][40][41][42] we observed in a previous study that exposure to adverse experiences during childhood is associated with poorer functional [25] and symptomatic [26] recovery; the fact that LO patients were more likely to have been exposed to trauma may hence play a role in their failure to return to their pre-morbid functional level.…”
Section: Discussionsupporting
confidence: 90%
“…However, due to power issues, multiple testing and to follow earlier research in our sample (Heins et al, 2011), we currently chose to use a division in abuse and neglect. Also, future studies may want to incorporate detailed information concerning the age at which childhood trauma occurred as this seems to impact functional outcome (Alameda et al, 2015).…”
Section: Discussionmentioning
confidence: 99%